Two distinct decadal and centennial cyclicities forced marine upwelling intensity and precipitation during the late Early Miocene in central Europe - Auer, G.; Piller, W. E.; Harzhauser, M. (Climate of the past, 2015)
Within a 5.5 m thick succession of Upper Burdigalian (Karpatian) sediments in the North Alpine Foreland Basin (NAFB; Austria), dated to CNP-zone NN4, a high-resolution section was logged continuously. One hundred samples were taken with a resolution of ~10 mm (approximating ~17 years) per layer and analyzed using an integrated multi-proxy approach. Earlier analyses of geochemistry and calcareous nannoplankton assemblages hint at small-scale, short-term variations in paleoenvironmental conditions, such as water-column stratification, primary productivity, organic matter flux, bottom-water oxygenation, freshwater influx, and changes in relative sea level. The results indicate a highly dynamic shallow marine setting that was subject to high-frequency environmental changes on a decadal to centennial scale. Time-series analyses on nine different proxy data sets using REDFIT analysis and wavelet spectra were applied to resolve a possible cyclic nature of these variations. Analyses revealed that different proxies for precipitation, upwelling intensity, and overall productivity were likely controlled by different cyclicities. A best-fit adjustment of the likely sedimentation rates within the high-resolution section resulted in periodicities fitting well with the Lower (~65 years) and Upper (~113 years) Gleissberg cycle as well as the Suess/de Vries cycle (~211 years). The section covers a time span of ~1190 years based on the correlation with solar cycles, which resulted in an estimated sedimentation rate of 575 mm kyr−1. For the first time, short-term climate variability on a decadal to centennial scale is resolved in Lower Miocene shallow marine laminated sediments in a land-based section. The results hint at a close relationship between climate variability and solar forcing during the Late Burdigalian. Moreover, accepting that these cyclicities are indeed of solar origin, this would indicate that precipitation was driven by the two Gleissberg cycles, while upwelling was driven by the Suess cycle. Furthermore, proxies for primary productivity were influenced by both cycles, although the Suess cycle exerts dominant control, reflecting a stronger influence of upwelling on primary productivity.